Performance of ground watermarkets in Pakistan - Meinzen-Dick, Ruth S. (Pakistan Institute of Development Economics, 1993)
Irrigation provides crucial water for agricultural production on over 80 percent of the gross cropped area in Pakistan. Most of this irrigation comes through public canal systems, but groundwater has become a crucial input, both as a sole source of irrigation and as a supplement to surface irrigation in canal irrigation commands. However, ownership of private tubewells is concentrated among large farmers: 70 percent of all tubewells are owned by farmers with over 12.5 acres and half are owned by farmers with over 25 acres, which seems "to point toward an adverse effect of private tubewells on income distribution within agriculture" [World Bank (1984), p. 35]. Institutional arrangements are needed to spread access to groundwater to other farmers, to increase agricultural productivity and improve equity in the use of irrigation water resources without overcapitalisation of agriculture. Water m~kets provide one of the most promising institutional mechanisms for increasing access to irrigation from private groundwater, for providing vertical drainage, and for increasing the efficiency of water use in irrigation systems see Rosegrant and Binswanger (1992). While such markets are not formalised or officially recognised, the sale of water from private tubewells is a growing form of private irrigation development. I This paper examines the nature and operation of markets for groundwater in Pakistan. It deals with the extent of water market development, who participates, and the effect of purchased irrigation on the productivity of irrigated agriculture. It concludes with policy issues for improving the performance of water markets.